Tradisi Kirab Hadeging Perdikan dan Dampaknya Terhadap Masyarakat Desa Tawangsari Kecamatan Kedungwaru Kabupaten Tulungagung Jawa Timur - Saputra, Zakaria; Rahmatullah, Asep; Wahyudin, Fatimahtus Zahro Nur (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
The Tawangsari Hadeging Perdikan Carnival tradition is an event to raise people's enthusiasm for knowing the origins of the village and the history of Tawangsari Village. The aim of conducting research on the Hadeging carnival tradition is to find out the history, implementation process and impact on society, and also to introduce local traditions to the people of Tulungagung. This study classifies field research into the type of cultural history research, which in the study uses four stages, namely, heuristics, criticism, interpretation, and historiography. This research can be found that, the history of the Tawangsari Hadeging Perdikan Carnival was held on April 23 2017. The Tawangsari Hadeging Perdikan Carnival came from Sentana Dalem's initiative to commemorate the ancestors of Tawangsari Village, Islamic broadcast media, and raise enthusiasm for getting to know the people from the village and their origins. history of Tawangsari Village. The implementation of the Hateging carnival began with a gathering of Tawangsari courtiers and representatives of the Yogyakarta sultanate in the pendhopo, continued to the Jami mosque to perform tahlil, prayers and send prayers, then everyone gathered to prepare for the carnival. The line contains the people of Tawangsari Village from various representatives, such as. a line of school children, RT representatives, arts groups, and a special line of mountain bearers. After the carnival, all participants gathered at the Tawangsari Jami' Mosque to listen to various remarks. Finished Finished, ended with praying together for the safety of the country, including Tawangsari Village, and continued with eating together and fighting over mountains as part of the blessing. The Tawangsari Hadeging Perdikan Carnival continued in the evening with a Ratiban and a big recital at the Tawangsari Jami' Mosque. The implementation of the Hadeging perdikan carnival has had an impact on various sectors, namely, the social sector, the religious sector, the education sector, the economic sector and the political sector.